Detection of Extended Spectrum Beta-Lactamases in Pseudomonas aeruginosa Isolates in a Tertiary Care Hospital - Aishwarya J. Ramalingam, Lakshmi Santhanam, Chitralekha Saikumar, V. Illamani (Journal of Applied Pharmaceutical Science, 2015)
The aim of the present study was to detect the extended-spectrum β-lactamase (ESBL) production among Pseudomonas aeruginosa isolates from various samples. A total of 125 Pseudomonas aeruginosa isolates from various samples in a tertiary care hospital from June 2014 to November 2014 were included in the study. The diagnosis was confirmed using standard bacteriological techniques and antibiotic susceptibility testing was done by Kirby Bauer disc-diffusion method. The isolates resistant to the third generation cephalosporins were tested for ESBL production using double-disc synergy test (DDST) using ceftazidime alone and combined ceftazidime-clavulanic acid discs. It was found that out of the 125 isolates tested, 17 (13.6%) were found to produce ESBL. Also, all the ESBL-producing P. aeruginosa were resistant to third generation cephalosporins and they were 100% susceptible to meropenem followed by 60% susceptibility to amikacin and 50% susceptibility to ofloxacin. This study emphasizes on the need for global control of antimicrobial resistance; and to create awareness among the clinicians and general population thereby reducing the mortality and morbidity associated with multi-drug resistant pathogens.